Single dendrite-targeting interneurons generate branch-specific inhibition - Stokes, Caleb C. A.; Teeter, Corinne M.; Isaacson, Jeffry S. (Frontiers in Neural Circuits, 2014)
Microcircuits composed of dendrite-targeting inhibitory interneurons and pyramidal cells are fundamental elements of cortical networks, however, the impact of individual interneurons on pyramidal dendrites is unclear. Here, we combine paired recordings and calcium imaging to determine the spatial domain over which single dendrite-targeting interneurons influence pyramidal cells in olfactory cortex. We show that a major action of individual interneurons is to inhibit dendrites in a branch-specific fashion.